Evaluation the efficacy of Ethanol Extract Derived from Wild Mint on the Life Parameters of the Aphis fabae (Hemiptera: Aphididae) (Sco-poli) under laboratory conditions - Al ouboodi , Amal Shkhair Younus; Mohammed , Akram Ali (Journal of Kerbala for Agricultural Sciences, 2023)
The black bean aphid, Aphis fabae is a significant economic pest with a global presence, impacting a wide range of plant species. This study aimed to assess the effectiveness of ethanol extract derived from wild mint (Mentha longifolia) under laboratory conditions on various life performance criteria of A. fabae. The evaluation involved measuring mortality rates of nymphs and adults, as well as adult productivity, utilizing three different extract concentrations (1%, 2%, and 3% w/v). The results revealed that the ethanol extract of plant leaves had a substantial effect on all life stages of the aphid, with a more pronounced impact observed at higher concentrations and longer exposure periods. In the first nymphal instar, the mortality rate reached 81% at a concentration of 3%, and in the second nymphal instar, it was 80% at the same concentration. For the third and fourth nymphal instars, the mortality rates were 82% and 82.5%, respectively, at a concentration of 3%. As for adult aphids, the mortality rate was 81.333% at a concentration of 3%. Moreover, the extract significantly reduced the productivity of adult aphids, with rates of 1.68%, 1.82%, and 1% at concentrations of 1%, 2%, and 3%, respectively.